Improving rice photosynthesis in suboptimal conditions - Herman Abdullah, Tiara (2020)
For plants grown in agriculture, productivity and yield are two consequential factors which must be maintained to ensure a continued supply of food for a burgeoning population. Rice is consumed in many regions in the world. The high-yielding rice genotypes cultivated today are the result of decades of breeding for shorter stems and leaves with more erect canopies that maximises grain number and weight. As we approach the theoretical upper limits of yield capacity set by the environment and crop genetics, increasing pressure has been placed on identifying the traits and mechanisms that would improve photosynthetic efficiency, both at the leaf and canopy levels. While rice is consumed in many locations of the world, it is mostly cultivated in tropical regions that are facing growing pressures both environmentally and economically. In Malaysia, rice is being cultivated in increasingly stressful environments, where the requirement for substantial amounts of nitrogen fertilisers is high. With the rising costs of fertiliser production and the increasing degradation of arable land, there is a need to select for more resilient rice varieties with improved photosynthetic efficiencies for cultivation in suboptimal conditions.